Philip DuMont letter to James Peters regarding Sparrow identification, November 23, 1933 - DuMont, Philip A. (Philip Atkinson), 1903-1996 (1933)
Letter from Philip DuMont to James Peters dated November 23, 1933. DuMont asks for assistance in correctly identifying Savannah Sparrow specimens and verifying Grasshopper Sparrow specimens. This document is answered by a letter from Peters: https://n2t.net/ark:/87292/w96688q00.